Performance of Sysmex UF-5000 for candiduria screening - İLKİ, ZEYNEP ARZU (My University, 2022)
In this study, we tested the performance of the Sysmex UF-5000 system to detect yeast-like cell (YLC) counting to screen for candiduria. Urine samples were screened for leukocyte and yeast amount by flow cytometry and results were compared with fungal culture results. A total of 56,749 urine samples were enrolled in this study. Urine culture and urinalysis of YLC data were used to evaluate the performance of YLC in diagnosing candiduria. Different cut-off values (YLC. 5, 10, 20, 50, 100/µl) were evaluated. Youden index was used to determine the ideal cut-off value, and the highest was 0.95 with 5 YLC/µl. When the cut-off value for YLC is 5 cells/µl, 95.15% of the samples were “negative” with flow cytometry and culture (NPV:100%). In conclusion, detection of YLC by flow cytometer (Sysmex UF-5000) can be a rapid alternative method to exclude candiduria prior to urine culture.